Pilot Project to Integrate Community and Clinical Level Systems to Address Health Disparities in the Prevention and Treatment of Obesity among Ethnic Minority Inner-City Middle School Students: Lessons Learned. (26th March 2018) - Rieder, Jessica; Cain, Agnieszka; Carson, Erica; Benya, Andrea; Meissner, Paul; Isasi, Carmen R.; Wylie-Rosett, Judith; Hoffman, Neal; Kelly, Colleen; Silver, Ellen J.; Bauman, Laurie J.
Abstract : Effective obesity prevention and treatment interventions are lacking in the United States, especially for impoverished minority youths at risk for health disparities, and especially in accessible community-based settings. We describe the launch and pilot implementation evaluation of the first year of the B'N Fit POWER initiative as a middle school-based comprehensive wellness program that integrates weight management programming into existing onsite preventive and clinical services. Consistent with the existing implementation science literature, we focused on both the organizational structures that facilitate communication and the development of trust among stakeholders, students, and families and the development of realistic and timely goals to implement and integrate all aspects of the program. New implementation and programming strategies were developed and tested to increase the proportion of students screened, support the linkage of students to care, and streamline the integration of program clinical and afterschool components into routine services already offered at the school. We report on our initial implementation activities using the Standards for Reporting Implementation Studies (StaRI) framework using hybrid outcomes combining the Reach element from the RE-AIM framework with a newly conceptualized Wellness Cascade.